2008
DOI: 10.1161/strokeaha.108.518357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carotid Artery Stenting and Carotid Endarterectomy in Cognitive Performance

Abstract: Background and Purpose-Change in cognition is being increasingly recognized as an important outcome measure; however, the role of carotid revascularization on this issue remains to be determined. It is still under debate whether carotid artery stenting and carotid endarterectomy have the same influence on neuropsychological functions. Summary of Review-This article systematically reviews recent literature in an attempt to clarify this issue. A total of 32 papers reporting on neurocognition after carotid endart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 50 publications
(145 reference statements)
9
118
1
5
Order By: Relevance
“…1,2 While CEA may also improve cognitive function, 3,4 cognitive impairment occurs in 10%-30% of patients following CEA. [5][6][7][8] A recent study reported that 11% of patients undergoing CEA experienced improvement in cognitive function after surgery, while another 11% experienced a decline in cognitive function after surgery.…”
Section: Abbreviationsmentioning
confidence: 99%
“…1,2 While CEA may also improve cognitive function, 3,4 cognitive impairment occurs in 10%-30% of patients following CEA. [5][6][7][8] A recent study reported that 11% of patients undergoing CEA experienced improvement in cognitive function after surgery, while another 11% experienced a decline in cognitive function after surgery.…”
Section: Abbreviationsmentioning
confidence: 99%
“…A recent study suggested that normalization of cerebral metabolism via improvements in cerebral hemodynamics after CEA may result in cognitive improvement as well as functional recovery of the neurotransmitter system. 5) Other investigators have hypothesized that cognitive impairment after CEA may result from three possible mechanisms 2,[6][7][8][9][11][12][13]18) : cerebral hemispheric hypoperfusion during ICA clamping, intraoperative gaseous and particulate emboli from the surgical site, and postoperative cerebral hyperperfusion. The present study showed no relationship between duration of ICA clamping or new ischemic lesions on postoperative diffusion-weighted imaging and postoperative cognitive change.…”
Section: Discussionmentioning
confidence: 99%
“…4) Numerous studies have investigated changes in cognitive function following CEA using objective neuropsychological testing and found that, while CEA may improve cognitive function, 9,17) cognitive impairment occurs in 10% to 30% of patients following CEA. 7,12,13,20) However, reports defined no clear criteria for determining significant cognitive improvement or impairment after surgery on neuropsychological test scores, because such postoperative changes may, in part, reflect the``practice effect'' (an improvement in scores when patients are repeatedly tested).…”
Section: Introductionmentioning
confidence: 99%
“…Because CEA can be performed on the left or right carotid artery, a number of studies have investigated whether the laterality of CEA plays a role in the kind of cognitive deficits a patient exhibits postoperatively. 7,14,24 Thus far, researchers have focused on the laterality of deficits after CEA in the verbal, 2,7,24 executive, 4,5,9,13,14 and visuospatial domains. 1,7,22 For example, postoperative language changes have been associated primarily with a left CEA.…”
mentioning
confidence: 99%
“…7,14,24 Thus far, researchers have focused on the laterality of deficits after CEA in the verbal, 2,7,24 executive, 4,5,9,13,14 and visuospatial domains. 1,7,22 For example, postoperative language changes have been associated primarily with a left CEA. 2,3,15,16,21,24 To the best of our knowledge, no previous studies have associated the laterality of CEA with its influence on subtle postoperative hand deficits of coordination.…”
mentioning
confidence: 99%